Study protocol: a non-randomised community trial to evaluate the effectiveness of the communities that care prevention system in Germany - Dominik Röding; Renate Soellner; Maren Reder; Vera Birgel; Constantin Kleiner; Maike Stolz; Frederick Groeger-Roth; Christian Krauth; Ulla Walter (BMC, 2021)
Abstract Background The Communities That Care (CTC) prevention planning and implementation system trains communities throughout a five-phase cycle to (1) build capacity for prevention, (2) adopt science-based prevention, (3) assess the prevention needs of adolescents living in the community, (4) select, and (5) implement evidence-based programs according to their needs. After CTC proved to be effective and cost-effective in the U.S., it is being used by an increasing number of communities in Germany. The aim of this study is to evaluate the effectiveness and cost-effectiveness of CTC in Germany. Methods Communities in CTC-phases 1 to 3 (n = 21) and individually-matched comparison communities (n = 21) were recruited for a non-randomised trial. To assess long-term outcomes, (1) a cohort of 5th Grade students will be surveyed biennially concerning behaviours (antisocial behaviour and substance use) and well-being as well as risk and protective factors. Additionally, (2) biennial cross-sectional surveys will be conducted in 6th, 8th, 10th, and 11th Grade in each community. To assess short-term outcomes, a cohort of ten key informants per community will be surveyed biennially concerning adoption of science-based prevention, collaboration, community support and community norms. (4) In a cross-sectional design, all ongoing prevention programs and activities in the communities will be assessed biennially and data will be collected about costs, implementation and other characteristics of the programs and activities. (5) To monitor the CTC implementation, the members of the local CTC-boards will be surveyed annually (cross-sectional design) about team functioning and coalition capacity. Data analysis will include general and generalised mixed models to assess the average treatment effect of CTC. Mediation analyses will be performed to test the logical model, e.g., adoption of science-based prevention as a mediator for the effectiveness of the CTC approach. Discussion This is the first controlled study to evaluate the effectiveness of a comprehensive community prevention approach in Germany. Evaluating the effectiveness of CTC in Germany is an important prerequisite for further diffusion of the CTC approach. Trial registration This study was registered with German Clinical Trial Register: DRKS00022819 on Aug 18, 2021.